10x=3x-18+12-6

Simple and best practice solution for 10x=3x-18+12-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x=3x-18+12-6 equation:


Simplifying
10x = 3x + -18 + 12 + -6

Reorder the terms:
10x = -18 + 12 + -6 + 3x

Combine like terms: -18 + 12 = -6
10x = -6 + -6 + 3x

Combine like terms: -6 + -6 = -12
10x = -12 + 3x

Solving
10x = -12 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
10x + -3x = -12 + 3x + -3x

Combine like terms: 10x + -3x = 7x
7x = -12 + 3x + -3x

Combine like terms: 3x + -3x = 0
7x = -12 + 0
7x = -12

Divide each side by '7'.
x = -1.714285714

Simplifying
x = -1.714285714

See similar equations:

| -8X+(2X-6)+(X+15)=12 | | (3n-1)(2n-1)=15 | | 8x+84=y | | 5x-3y=-72 | | 0.11x+4=8-0.4x | | 0.2x+2.4x=9.1-1.7+2.4x | | 0.45x+0.10(250-x)=49.5 | | 3x+2y+6z=0 | | d/dx(3y-2x=6y-6xy) | | 0.4-4+7-0.9y= | | 12a*12a= | | 12a^2*2= | | 15/12=21/x | | -0.7x=2.8 | | n(n+2)+n+2=12 | | 3.6g+2=1.6g+12 | | 12w=10+9 | | 2(n-1)(2n-1)+3n-1(n+1)=21 | | 6n+2=398 | | 8a+10a=10 | | 5x+18-4x=-3+(-10) | | 4s+6c=45 | | 5n-7=12 | | -81=27 | | 3+c=4+1 | | 5n-7=14 | | 5n-7=10 | | 3s+5c=34 | | 4(8x+5)-10(5x+2)= | | 5n-7=40 | | (2+4n)+(9+2y)= | | 12=4+v |

Equations solver categories